Literackość w encyklikach Jana Pawła II = Literariness of the Encyclicals of John Paul II - Ołdakowska-Kuflowa, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Holy Father John Paul II was the author of literary works and theological texts, fourteen encyclicals included, which had the status of papal documents. The presence of literary features in the important documents of papal teaching is a perceptible phenomenon. The first part of the following study points out how the Pope appreciated culture and art in his encyclicals. The second part of the study contains the analysis of the encyclicals with respect to language, stylistic devices, references to literature, parallelism of poetic works of Karol Wojtyla - John Paul II and appropriate fragments of encyclicals. Finally, poetic prayers by the Holy Father, which crown his documents, have been discussed.
Keywords: Jan Paweł II, papież (1929-2005); encykliki; analiza językowa